Proceedings of the SIGCHI Conference on Human Factors in Computing Systems - CHI '98 1998
DOI: 10.1145/274644.274706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interfaces for annotation on communication in a collaborative task

Abstract: Various interfaces exist for annotations. Little is known, however, about how such interface variations affect communication. We designed an annotation interface intended to facilitate annotation and undertook a study to compare this interface to two commonly used alternatives. Results support the hypothesis that annotation interfaces affect the number and types of problems about which collaborators communicate. Results also suggest the need for more research on interface effects within other communicative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…The results presented in this study partially overlap with those of Wojahn et al [34]. In their study on the effects of annotation interfaces on collaborative writing, the authors found that participants in the interlinear and aligned conditions, which can be mapped to our ShS and CoC conditions, communicated about significantly more problems than those in the split-screen condition (our MSN or EC condition).…”
Section: Qualitative Descriptionssupporting
confidence: 72%
“…The results presented in this study partially overlap with those of Wojahn et al [34]. In their study on the effects of annotation interfaces on collaborative writing, the authors found that participants in the interlinear and aligned conditions, which can be mapped to our ShS and CoC conditions, communicated about significantly more problems than those in the split-screen condition (our MSN or EC condition).…”
Section: Qualitative Descriptionssupporting
confidence: 72%
“…A range of important studies were performed with pre-Web annotation systems. For example, (Wojahn et al, 1998) studied the effect of an annotation interface on collaboration by comparing three different annotation interfaces. They concluded that annotation interfaces affect the number and types of problems about which collaborators communicate.…”
Section: Web Annotation and Collaborative Workmentioning
confidence: 99%
“…Many techniques and frameworks offer different approaches to eliciting culture and context in Information and Communication Technologies (ICT) design [9,10,26]. These approaches have the merit of viably exploring elements of the problem domain within the complexity of collaborative design settings.…”
Section: Introductionmentioning
confidence: 99%